The effects of widespread adoption of climate-smart agriculture in Africa south of the Sahara under changing climate regimes - De Pinto, Alessandro; Kwon, Ho Young; Cenacchi, Nicola; Dunston, Shahnila (International Food Policy Research Institute, 2017)
Chapter 3 shows the benefits of CSA adoption but also its limits when the approach is interpreted in a restrictive way and applied only to crop production.